Optical and Electrophysical Properties of the Germanium Oxynitride Dielectric Films - Nakhutsrishvili, Irakli; Kokhreidze, Revaz; Adamia, Zurab; Loria, Lasha (Scientific Research, New Technologies and Applications Vol. 7, 2024)
The work studied the optical and electrophysical characteristics of dielectric films of germanium oxynitride obtained by nitridation of single-crystalline germanium with humid ammonia or hydrazine vapors and deposition of reaction products on semiconductor substrates. The technological method described in our previous work was used. Germanium oxynitride films create a high-quality interface with silicon and indium phosphide. In recent years, very few works have been published on this topic and an attempt was made to fill this gap. It was shown that the capacitance-voltage characteristics of the GexOyNz – Si structure have hysteresis. These structures can be used to store charge in memory elements. The C-U characteristics of the GexOyNz – InP structure in the frequency range of 20 Hz – 20 MHz have very low-frequency dispersion. This defines the prospect of using the structure for creating MIS devices and integrated circuits.